The Northward Range Shifting of Agapanthiola Leucaspis Under the Climate Change - Viznovych, Violetta; Zamoroka, Andrew (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
Agapanthiola leucaspis is a steppe transpalearctic cerambycid species, widely distributed from the Pannonian lowland in Europe to the Mongolian plateau in Asia. In Ukraine, the species was previously known from the Pontic Plains and the Crimean Peninsula. However, in the last decade, a number of new localities of A. leucaspis have been discovered far outside the original range. We previously hypothesized a possible link between the northward spread of A. leucaspis and the current climate change. In this paper, we tested this hypothesis using computer simulations with GIS technologies. Our primary objective was to determine the critical value of key climatic factors that could potentially trigger the northward and montane range expansion of A. leucaspis. We collected all available data, including our own materials, scientific collections, published scientific papers, and citizen science data on the distribution of A. leucaspis in Ukraine and neighboring countries. These data were separated by the time of records before 2000 and after 2000 according to the change of the current understanding of climatic norm of 1950-2000 due to global warming. As a result, we determined the ecological valency of A. leucaspis in relation to climatic factors and built a model of its original range. Further simulations were associated with a +2.0°C change in global temperature parameters in 0.5°C increments and a 30% increase and decrease in precipitation in 10% increments. Resultantly, we found that the amount of precipitation and the seasonality of temperatures, especially in winter, are crucial factors for the observed fluctuation of A. leucaspis range. An increase in average temperatures eliminates the winter frosts which are limiting factor for the spread of A. leucaspis to the north. The decrease in average annual precipitation increases the probability of the species survival in areas where this was previously impossible. We have shown that to expand the current range of A. leucaspis, it is enough to warm the climate in the annual average by +0.5°C and reduce the amount of precipitation by 10%. A warmer and drier climate is the main abiotic factor for the expansion of A. leucaspis into higher latitudes and mountains.